2020
DOI: 10.1016/j.jceh.2019.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Genotype 1 and 3 Response to Velpatasvir and Sofosbuvir in Chronic Hepatitis C in the Kashmiri Population: An Observational Study

Abstract: Background: Our data is one of the earliest study from the Indian subcontinent on Velpatasvir/Sofosbuvir (VEL/ SOF) combination in chronic hepatitis C (CHC). The primary end point was to evaluate sustained virologic response (SVR) 12 in CHC-infected patients and to determine its effect in patients with hepatitis C virus-related cirrhosis. The secondary end point was to observe any adverse events related to treatment. Methods: All patients with CHC were randomized into two groups: noncirrhotic and cirrhotic. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…15 Another Indian study conducted in 100 HCV-infected patients has demonstrated SVR 12 rates of 99%. 16 Compared with the FDA registration trials and other real-world studies, the SVR12 rates in the current study were marginally less. However, the sensitivity analysis conducted using the LOCF approach, complete case, and PPS showed SVR12 response rates of 94.8%, 93.9%, and 94.4%.…”
Section: Discussionmentioning
confidence: 51%
“…15 Another Indian study conducted in 100 HCV-infected patients has demonstrated SVR 12 rates of 99%. 16 Compared with the FDA registration trials and other real-world studies, the SVR12 rates in the current study were marginally less. However, the sensitivity analysis conducted using the LOCF approach, complete case, and PPS showed SVR12 response rates of 94.8%, 93.9%, and 94.4%.…”
Section: Discussionmentioning
confidence: 51%